2011
DOI: 10.1111/j.1540-8175.2011.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler and Strain Rate Imaging Detect Improvement of Myocardial Function in Iron Deficient Patients with Congestive Heart Failure after Iron Replacement Therapy

Abstract: Correction of iron deficiency improves functional class and walking distance in nonanemic iron deficient patients with systolic heart failure. Tissue Doppler and strain rate demonstrated a significant improvement of diastolic and systolic function after therapy despite lack of improvement of ejection fraction. (Echocardiography 2012;29:13-18).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 30 publications
5
69
2
Order By: Relevance
“…Our results suggest that iron treatment does have a large effect on both sFe (Hedges’ g=0.966, p<0.001; figure 4) and Tsat (Hedges’ g=0.730, p<0.001; figure 3). However, this finding should be interpreted with caution if one intends is to use these measures to indicate iron status or a positive response to treatment because some individual studies showed no change after treatment 15 19 25 27 28 31 34 35 39 41. The treatment failure common to these studies suggests that the IDNA was not severe enough for an intervention to impact iron status.…”
Section: Discussionmentioning
confidence: 94%
“…Our results suggest that iron treatment does have a large effect on both sFe (Hedges’ g=0.966, p<0.001; figure 4) and Tsat (Hedges’ g=0.730, p<0.001; figure 3). However, this finding should be interpreted with caution if one intends is to use these measures to indicate iron status or a positive response to treatment because some individual studies showed no change after treatment 15 19 25 27 28 31 34 35 39 41. The treatment failure common to these studies suggests that the IDNA was not severe enough for an intervention to impact iron status.…”
Section: Discussionmentioning
confidence: 94%
“…Cardiac magnetic resonance imaging studies show that low myocardial iron (as measured by myocardial T2* imaging) was associated with non-ischaemic heart failure (Nagao et al, 2014(Nagao et al, , 2015 While there may be multiple pathways through which iron deficiency can impair cardiac function, tissue Doppler and strain rate measurements show significant improvements in diastolic and systolic myocardial function in iron-deficient patients after iron replacement therapy (Gaber et al, 2012).…”
Section: Pathophysiology Of Iron Deficiency In the Failing Heartmentioning
confidence: 99%
“…Gaber et al , found that correction of iron deficiency improves functional class and walking distance in non-anemic iron deficient patients with systolic HF. 24 They also found significant improvement of diastolic and systolic function using echocardiogram after therapy despite lack of improvement of LVEF. 24 Ongoing clinical trials are addressing the role of iron supplementation in both anemic and non-anemic patients with HF.…”
Section: Discussionmentioning
confidence: 92%